Studi Ekologi Komunitas Biotik Menggunakan Metode Relevé pada Berbagai Tipe Habitat di Kabupaten Polewali Mandar - Ratna Sari (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the structure and composition of biotic communities in various habitat types in Polewali Mandar Regency, West Sulawesi, using the relevé method. Observations were carried out in five sub-districts, namely Campalagian, Binuang, Tutar, Tapango, and Limboro. At each location, three plot sizes (1×1 m, 3×3 m, and 5×5 m) were set to compare species diversity based on the size of the sampling area. Data is collected by recording the presence of all organisms (plants and animals) present in the plot without counting the number of individuals in detail. The results showed that the number of species increased as the area of the plot increased, with a range of 3-7 species on a 1×1 m plot, 5-15 species on a 3×3 m plot, and 9-26 species on a 5×5 m plot. Several groups of organisms, such as pioneer herbaceous plants, shrubs, and generalist insects (e.g., Formicidae and Lepidoptera) were detected consistently across a wide range of plot sizes and habitats, indicating adaptability and wide distribution. Increased species richness on larger plots reflects the heterogeneity of microhabitats and the greater complexity of trophic interactions, thus supporting the principle of species-area relations in community ecology. This study provides basic data on biodiversity and biotic community structure in Polewali Mandar that can be used as a reference in conservation planning, sustainable natural resource management, and ecological policy development at the regional level.